Development of English-Indonesia Idiom Mobile Dictionary Using Optical Character Recognition - Robby Kurniawan Budhi; Dwi Taufik Hidayat; Jonathan Putra Pangapul (Jurnal Transformatika, 2018)
Idioms are phrases that often have different meanings with their literal meaning. The combination of words used, will have different meaning if translated one by one, especially for English words. Currently there are many idiom dictionary applications that exist, but the users have to type the words as the input manually. This requires more precision and time, especially for users who are less fluent in English. To speed up the search process and reduce errors that may occur, optical character recognition methods are used in this study. Through testing and observation to the user, it can be concluded that this application is able to help users to find translations of idioms in English more quickly and precisely.